The effect of capital structure on performance of insurance companies: Evidence from Jordan - Zelhuda, Shamsuddin; Mohannad, Almajali (2019)
The relationship between capital structure and profit cannot be ignored because the improvement in profitability is essential for the company to continue its business. The objective of the paper to examine the relationship between capital structures on the profitability of the Jordanian insurance firms. A sample of 19 insurance firms listed on the Amman Stock Exchange for a period of 10 years from 2008 – 2017 was selected. The regression analysis and correlations are used to estimate the functions relating to profitability that measured by return on equity (ROE) and Tobin's Q, with measures of capital structure: Short term debt (STD), Long term debt (LTD) and Equity financing (TQ). Also, inflation rate and sales growth are used as control variables. Empirical results show (STD) and (LTD) are positively correlated with the (ROE) while negatively correlated with Tobin's Q, (ETQ is positive correlated with all profitability measures, the result also shows that financial leverage is positively significant to profitability. The results confirmed that an increase in leverage position is associated with an increase in profitability.